1998
DOI: 10.1111/j.1399-302x.1998.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific T‐cell receptor Vβ expression in Porphyromonas gingivalis–specific T‐cell lines

Abstract: FACS analysis was used to determine the expression of 15 T-cell receptor V beta families on CD4 and CD8 cells in Porphyromonas gingivalis specific T-cell lines established from eight P. gingivalis-positive adult periodontitis and seven P. gingivalis-positive healthy or gingivitis subjects. All 15 T-cell receptor V beta families were expressed by the T-cell lines, although a significantly higher proportion of the CD4 cells expressed the 5.2-3 V beta region compared with the other 14 families, including the 5.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
3
16
1
Order By: Relevance
“…Finally, there was an overexpression of the TCR V␤5.2 family in all lines. The cytokine, chemokine, and V␤ results are similar to those demonstrated previously for P. gingivalis-specific lines from periodontal disease patients (10)(11)(12). Taken together, these results give strong support to the hypothesis (40) that cross-reactivity of the immune response to bacterial HSPs, including those of periodontal pathogens, with arterial endothelial cells expressing hHSP60 may be a mechanism involved in the disease process of atherosclerosis at least in some patients.…”
Section: Vol 12 2005 Hsp-specific T Cells In Atherosclerosis 265supporting
confidence: 78%
See 1 more Smart Citation
“…Finally, there was an overexpression of the TCR V␤5.2 family in all lines. The cytokine, chemokine, and V␤ results are similar to those demonstrated previously for P. gingivalis-specific lines from periodontal disease patients (10)(11)(12). Taken together, these results give strong support to the hypothesis (40) that cross-reactivity of the immune response to bacterial HSPs, including those of periodontal pathogens, with arterial endothelial cells expressing hHSP60 may be a mechanism involved in the disease process of atherosclerosis at least in some patients.…”
Section: Vol 12 2005 Hsp-specific T Cells In Atherosclerosis 265supporting
confidence: 78%
“…The V␤13 family appeared also to be more highly expressed. The V␤5.2 region has previously been shown to be preferentially expressed by CD4 and CD8 cells in P. gingivalis-specific T-cell lines established from peripheral blood of both adult periodontitis and control subjects, and this overexpression of certain V␤ families was shown to be due to antigen-specific rather than superantigen activation (11).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, which is consistent with an earlier study (19), we demonstrated that certain clinical strains of P. intermedia have the ability to preferentially activate the expression of CD4 ϩ T cells. Recent studies have shown that P. gingivalis, another periodontal pathogen, also causes the expansion of the population of V␤-specific T cells (8,37). We were unable to detect such expansions, which may be attributable to the types of strains that were used and/or whether the T cells used were antigen specific.…”
Section: Fig 2 P Intermedia-induced Proliferation Is T-cell Specifcontrasting
confidence: 47%
“…In this regard, there are reports suggesting that lipopolysaccharides (LPS) (11,30,31) and other surface components (12,21,29) isolated from P. intermedia are capable of inducing inflammatory lymphokines, which may contribute to the pathological inflammatory mechanisms that are operative in periodontal disease. Recently, there has been evidence to suggest that some periodontopathic organisms may be involved in the activation of T cells expressing specific variable regions on the ␤ chain (V␤) of T-cell receptors (TCRs) (8,19,20,37). One study showed that up to 50% of all gingival T cells express unique subsets of V␤ TCRs in most periodontitis patients but not in healthy subjects (37).…”
mentioning
confidence: 99%
“…These LCL were prepared as described previously (Gemmell et al, 1998(Gemmell et al, , 1999 and used to stimulate the P. gingivalis-specific T-cell lines at least 3 times (5-6 wks in culture). We stained the T-cells again to determine the cytokine profiles of each line.…”
Section: Subsequent Use Of Lcl As Apc To Present P Gingivalis Antigementioning
confidence: 99%